Coffee, tea, and plasma cholesterol: the Jerusalem Lipid Research Clinic prevalence study. Issue 6497 (14th September 1985) - Kark, J D; Friedlander, Y; Kaufmann, N A; Stein, Y
Abstract : The association of intake of coffee and tea, assessed by 24 hour dietary recall, with plasma cholesterol and its lipoprotein fractions was studied in a sample of 1007 men and 589 women aged 35-64 resident in Jerusalem. These cross sectional data showed a significant linear association (p less than 0.001) between consumption of coffee in men and plasma cholesterol and low density lipoprotein cholesterol concentrations. Men who drank five cups of coffee or more had plasma cholesterol concentrations about 0.5 mmol/l (20 mg/100 ml) higher than non-drinkers after controlling for age, ethnicity, body mass, education, season of year, smoking, tea drinking, and dietary intake of fat and carbohydrates. In women adjusted mean plasma cholesterol concentration was 0.34 mmol/l (13 mg/100 ml) higher in coffee drinkers grouped together (p less than 0.01). The test for a linear trend was not significant. The association in both sexes was largely with the low density lipoprotein cholesterol fraction. High density lipoprotein cholesterol concentrations were somewhat increased in women who drank coffee (p less than 0.01 for a linear trend) but not in men. Tea drinking was not associated with unadjusted plasma cholesterol concentrations in either sex. Male tea drinkers, but not female, had slightly higher adjusted plasma cholesterol concentrations than non-drinkers (0.15 mmol/l (6 mg/100 ml), p = 0.04). No dose response relation was evident. In this population, characterised by a low intake of saturated fatty acids and relatively low mean plasma cholesterol concentrations, coffee drinking may be a determinant of low density lipoprotein cholesterol concentrations.